Dental Anxiety and association with psychological sympyoms among adults attending IIUM Kuantan health facilities - Mohd, Farah Natashah; Said, Abdul Hadi; maluin, nur afirah; A.Rahaman, nabila; Ibrahim, Nurul Ruziantee (2021)
Introduction: There was dearth evidence on prevalence of dental anxiety among general population and its associated factors. Most researchers in Malaysia focused on undergraduates and pregnant mothers. Therefore, the objective of this study is to assess the prevalence of dental anxiety among general adult population in Kuantan, Malaysia and its associated factors, mainly with psychological symptoms and dental attendance patterns. Material and methods: This was a cross sectional study done among 465 adults attending IIUM Medical Center and Family Health Clinic in Kuantan, Malaysia. Participants were required to answer validated, self-administered questionnaires which consist of Depression Anxiety and Stress Scale (DASS), Modified Dental Anxiety Scale (MDAS) and Adult Dental Health Survey questionnaire. Data was analysed using Chi-square and Mann-Whitney test. Multiple logistic regression was used to determine the relationship between dental anxiety and other variables. Results: The prevalence of dental anxiety among respondents was very high (93.1%). It was found that female gender was 2.3 times more likely to have dental anxiety compare to male. Meanwhile, increase in age by 1 year reduced the likelihood to have dental anxiety by 3%. However, there was no significant association found between dental anxiety with psychological symptoms and dental attendance pattern. Conclusion: Majority of adults in Kuantan has dental anxiety. Factors such as age and gender are directly associated with dental anxiety in which female and younger age are more likely to have dental anxiety.However, dental anxiety is not associated with their anxiety, depression and stress symptoms.